Reinventing traditional Malay house for sustainable housing design: Obstacle and proposed solution - Ibrahim, Siti Halipah; Liew, A.A.H; Mohd Nawi, Mohd Nasrun; Yusoff, Mohd. Nazaruddin (Penerbit UTM Press, 2014)
Traditional Malay House design has the key of energy efficiency dwelling to create a sustainable housing. Today, modern houses are massively built replacing the Malaysia’s heritage house.Despite of this rapid development, the owners are aware on the drawback of this type of houses.Therefore, this study is conducted to investigate factors of developers reluctant to build the Traditional Malay House and correct the public misconception toward the housing perception.Survey questionnaire and in-depth interview were conducted.The results indicate that costing is the major problem for housing developers to construct Traditional Malay House.